The Level of Thiol‐Oxidised Plasma Albumin Is Elevated Following a Race in Australian Thoroughbred Horses - Christopher James; Erin M. Lloyd; Peter G. Arthur (Veterinary Medicine and Science)
ABSTRACT Background The extent to which muscle strain or tears are affecting race performance in horses is unknown because it is difficult to objectively identify muscle damage. One approach includes the use of physiological markers in blood. Recently, we linked the level of plasma thiol‐oxidised albumin, an oxidative stress biomarker, to muscle damage in humans. Objectives This aim of this work was to investigate whether the level of plasma thiol‐oxidised albumin was elevated in the days following a thoroughbred horse race. Study design ‘In vivo’ experiments. Methods Blood collection was performed by each trainer at their respective stable. Dried blood samples were collected for the level of thiol‐oxidised albumin before and each day for 7 days post‐race. Liquid blood samples were collected for analysis of the muscle enzymes creatine kinase (CK) and aspartate amino transferase (AST) before and on Day 2 and 5 post‐race and were analysed by external pathology centre. Results The level of thiol‐oxidised albumin peaked at 2 days post‐race, increasing by 3.9 ± 0.7% (p < 0.0001) and returned to pre‐race levels by Day 5. Thiol‐oxidised albumin also correlated with the activity of AST (R2 = 0.2, p = 0.01). The time of recovery for thiol‐oxidised albumin varied between individual horses, some recovered at Day 3 post‐race whereas others extended beyond 7 days post‐race. Main limitations No histological or imaging diagnosis was conducted to confirm that horses with elevated levels of thiol‐oxidised albumin also had definitive evidence of muscle damage. The activity of CK and AST was not measured daily, as was the case for the level of thiol‐oxidised albumin. Conclusions The level of thiol‐oxidised albumin has the potential to be useful in managing recovery and return to training or competition in horse following a bout of damaging exercise, particularly given the ease of collecting small serial small blood samples.